2021
DOI: 10.3390/cancers13061388
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Immune Checkpoint Inhibitors for Patients with Advanced Non Small-Cell Lung Cancer in Real-World: Review and Meta-Analysis

Abstract: Immunotherapy based on anti PD-1/PD-L1 inhibitors is the new standard of advanced non-small cell lung cancers. Pembrolizumab, nivolumab and atezolizumab are used in clinical practice. The strict eligibility criteria of clinical trials do not allow researchers to fully represent treatment effects in the patients that will ultimately use these drugs. We performed a systematic review and a meta-analysis to evaluate the effectiveness and safety of these drugs, and more generally of ICIs, as second-line therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
5
21
0
Order By: Relevance
“…In recent years, the use of ICIs for the treatment of NSCLC has considerably increased. Monoclonal antibodies that target the programmed cell death protein 1/programmed death-ligand 1 (PD-1/PD-L1) axis have been approved as first-and second-line treatments for advanced NSCLC worldwide (12). So far, several clinical trials have reported the efficacy and safety of neoadjuvant immunotherapy (13)(14)(15)(16)(17)(18) or chemoimmunotherapy (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) in stages I-III NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of ICIs for the treatment of NSCLC has considerably increased. Monoclonal antibodies that target the programmed cell death protein 1/programmed death-ligand 1 (PD-1/PD-L1) axis have been approved as first-and second-line treatments for advanced NSCLC worldwide (12). So far, several clinical trials have reported the efficacy and safety of neoadjuvant immunotherapy (13)(14)(15)(16)(17)(18) or chemoimmunotherapy (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) in stages I-III NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…While other MAs have evaluated the efficacy and/or safety of anti-PD-L1-containing strategies [ 7 , 8 , 9 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], to date this is the first safety MA to include studies evaluating first-line single immunotherapy agents in NSCLC patients with a PD-L1 positive expression enriched design.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, anti-PD-L1 monotherapy resulted in significantly longer overall survival and progression free survival in advanced NSCLC patients with high PD-L1 expression compared to chemotherapy alone, thus supporting the potential of this therapeutic option as a first-line strategy for this subgroup of patients [ 9 ]. In the past few years, several studies have focused on the efficacy and safety of PD-1/PD-L1 inhibitor agent immunotherapies [ 7 , 8 , 9 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, no safety comparisons evaluating first-line monotherapy with anti-PD-L1 agents in NSCLC patients with a PD-L1 positive expression enriched design have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…And in real-world head-to-head comparison in metastatic melanoma for frontline therapy, efficacy of nivolumab was similar to that of pembrolizumab and no significant difference in OS was observed ( Moser et al, 2020 ). Furthermore, a meta-analysis that enrolled 32 studies of daily clinical practice demonstrated anti-PD-1 and anti-PD-L1 immunotherapy provided survival benefits as sconed-line treatment of NSCLC, in which the median PFS and OS were 3.35 and 9.98 months, respectively ( Mencoboni et al, 2021 ). Although most patients enrolled in this meta-analysis were treated with nivolumab, the efficacy in clinical practice is comparable to that in clinical trials.…”
Section: Clinical Use Efficacy and Safetymentioning
confidence: 99%